Evaluation of 2,3-butanediol derived from whey fermentation as an effective bio-based monomer for waterborne polyurethane dispersions - Germán-Ayuso, Lorena; Cobos, Rubén; Lorenzo, Leire; Río, Francisca; Prieto-Fernández, Soraya; Roncal, Tomás; Cuevas, José M. (Frontiers in Chemistry, 2025)
Within the context of the circular economy, the transformation of agri-food waste or by-products into valuable products is essential to promoting a transition towards more sustainable and efficient utilisation of resources. Whey is a very abundant by-product of dairy manufacturing. Apart from partial reutilisation in animal feed or some food supplements, the sustainable management and disposal of whey still represent significant environmental challenges. In this work, whey is considered a valuable resource for producing high-value products, specifically 2,3-butanediol (2,3-BDO), which was produced through fermentation using the bacterial strain Lactococcus lactis 43103. The described process yielded a >90% purity of 2,3-BDO, which was evaluated as a potential chain extender in the synthesis of bio-based waterborne polyurethane dispersions (PUDs). The incorporation of whey-derived 2,3-BDO led to the development of PUDs with up to 90% bio-based content without detrimental effects on the process or liquid-phase properties. The combination of 100% bio-based polyether polyols with partially renewable L-lysine ethyl ester diisocyanate and whey-derived 2,3-BDO as a chain extender generated totally stable, low-particle-size water dispersions of amorphous polymers characterised by similar structure and molecular weight compared to those of alternative petroleum-based PUDs. These results open up the possibility of incorporating fermentation-derived 2,3-BDO as a totally renewable component in bio-based PUDs as potential sustainable resinous systems for further formulation of water-based coatings or adhesives.